Valanidou, Lilian - (:unkn) unknown (My University, 2026)
Lilian Valanidou is currently a PhD candidate in the field of Air Pollution Management, under the supervision of Dr. Costas N. Costa at the Department of Environmental Management of the Cyprus University of Technology (CUT). She has conducted her studies in Environmental Engineering at the Technical University of Crete (Greece) and has graduated in 2008 with a high grade point average. She has a Master’s degree in Environmental Engineering from the Environmental Engineering Department of the Technical University of Crete. In February 2009 she was admitted at CUT as a trainee and PhD candidate at the Laboratory of Waste Treatment. Her research interests lie in the domains of Environmental Management, Prevention of Pollution, Environmental Impact Studies and treatment of liquid, solid and especially gaseous pollutants. Patent: L.Y. Valanidou, C.P. Theologides, P.G. Savva and C.N. Costa, “Novel Catalyst Ag/MgO-CeO2-Al2O3 for the Low-temperature Ethanol-SCR of NO under lean de-NOx Conditions”, European Patent No. 1039001.5/EP1039001